Gender-specific associations of socioeconomic factors and obesity among urban adults in Turkey - Fitzgerald, Nurgul; Turnagol, Husrev; Basoglu, Sevil; Kosar, Nazan (Federation Amer Soc Exp Biol, 2013)
[Abstract Not Available]
Joint Annual Meeting of the ASPET/BPS at Experimental Biology (EB) -- APR 20-24, 2013 -- Boston, MA